BETWEEN "IMPORTANCE OF THE ACT OF READING" AND "THE PEDAGOGY OF AUTONOMY": EXPERIENCE REPORT ON A TAX TO PAULO FREIRE - Lima, Diva (2022)
This report describes the actions related to the Tribute to Paulo Freire, made from April to September 2021, by the Regional Education Development Coordination (CREDE 15), located in the municipality of Tauá, in the interior of Ceará. The objective of the experience was to develop a training action for teachers and school administrators, to honor Paulo Freire and highlight the value of his legacy to education, considering the challenging context of the Covid 19 pandemic, as well as the attacks on his memory, philosophy and pedagogy.Were done remote meetings were held through the Google Meet Platform, which contemplated the reflections on Paulo Freire's biography and legacy for education, focusing on the collective and dialogued analysis of two of his works: The importance of the act of reading and Pedagogy of Autonomy. For the accomplishment of the tribute, we had the involvement of 45 educators and we used as methodology the dialogic get-togethers on the selected works and the talk teacher session!. We defend that it is important to instigate reading spaces for studies and appreciation of the Freirean legacy, especially for the training of educators, in view of the chaotic Brazilian political and social scenario in which we are located today. We were moved by the idea that this experience is a way to “hope” in the face of the challenges that are posed.